2016
DOI: 10.14260/jemds/2016/595
|View full text |Cite
|
Sign up to set email alerts
|

A Clinical and Radiological Profile of Patients of Interstitial Lung Diseases, Attending the Chest Hospital of Medical College From North India

Abstract: OBJECTIVETo know the clinical and radiological profile of patients of Interstitial Lung Diseases attending the Chest

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Other studies from western countries also report more than 70% patients of sarcoidosis to be of less than 40 years of age. 5,15 In 11 in which they also observed cough and breathlessness as most common presenting symptoms in sarcoidosis. Also, in a study done by Kumar et al 10 the most common presenting symptom was found to be cough, which was present in 131 (89.7%) patients, followed by exertional dyspnea in 102 (69.9%).…”
Section: Resultsmentioning
confidence: 97%
“…Other studies from western countries also report more than 70% patients of sarcoidosis to be of less than 40 years of age. 5,15 In 11 in which they also observed cough and breathlessness as most common presenting symptoms in sarcoidosis. Also, in a study done by Kumar et al 10 the most common presenting symptom was found to be cough, which was present in 131 (89.7%) patients, followed by exertional dyspnea in 102 (69.9%).…”
Section: Resultsmentioning
confidence: 97%